Genome-wide identification of selection signals in fat-tailed and thin-tailed sheep populations - Gao, Lei; Zhang, Yiyuan; Zhang, Bin; Peng, Weifeng; Liu, Yucheng; Zhang, Zhenliang; Wang, Jingjing; Wan, Pengcheng; Yang, Hua; Zhao, Zongsheng (Frontiers in Genetics, 2025)
IntroductionIn the evolutionary context of sheep, the development of fat tails represents an adaptive survival mechanism in response to varying food availability. Despite food resource instability, sheep store energy by accumulating tail fat to survive periods of famine. This energy storage function remains present in domesticated sheep, serving as a key evolutionary reason for the formation of sheep tail fat.MethodsHere, we conducted whole-genome resequencing of 555 sheep samples (30 samples were newly sequenced and 525 were retrieved from published data) globally to investigate selection signatures associated with fat-tailed traits using Fixation Index (FST), Nucleotide diversity (π), cross-population composite likelihood ratio (XP-CLR), and runs of homozygosity (ROH) methods.Result and discussionOur examination of selection signatures in Fat-tailed and Thin-tailed Sheep Populations identified 32 candidate genes, with 6 genes (PDGFD, BMP2, GLIS1, LIPE, MSRB3, and TBX15) implicated in fat accumulation and lipid metabolism. Notably, 8 significant Gene Ontology terms (mesenchymal cell differentiation, positive regulation of ERK1 and ERK2 cascades, hormone metabolic process, nucleocytoplasmic transport, regulation of hormone levels, response to growth factor, regulation of canonical Wnt signaling pathway, and tissue morphogenesis) may play a role in fat deposition and tail fat development. These results will provide molecular targets for low-fat sheep breeding and enhance economic returns in sheep farming.ConclusionThis study will play a crucial role in environmental adaptation and product development, comprehensively driving the development of the sheep farming industry and enhancing economic benefits.